Sanitation Compliance and Its Determinants in a Barangay Community: Insights from Northern Mindanao - Araune, Paolo (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: Proper sanitation practices are crucial for public health, especially in regions with limited access to clean water. Objective: This study aimed to assess sanitation compliance among residents in a barangay in Northern Mindanao. It investigated the influence of age, education, gender, and socio-economic status on sanitation compliance. Methods: This descriptive study assessed sanitation compliance among barangay residents in Northern Mindanao. Simple random sampling was used; 231 respondents aged 21 to 60 Results: Significant differences were observed in compliance with sanitation practices based on age, particularly regarding water facilities and use. However, no significant difference was found for sanitation facilities and use. Educational attainment did not influence compliance with either water or sanitation practices. Gender did not significantly impact compliance with sanitation practices for water and sanitation facilities and use. Socio-economic status significantly differed in compliance with water facilities and use, but not for sanitation facilities and use. Conclusion: While age impacted compliance with water facilities, educational attainment did not show a significant effect. Gender also did not influence compliance significantly. However, socio-economic status notably affected compliance with water facilities. These insights highlight the importance of targeted interventions to improve sanitation practices across different demographic groups, ultimately enhancing community health and well-being. Recommendation: Clinical practitioners should focus on targeted interventions tailored to specific demographic groups, particularly addressing age-related factors affecting compliance with water facilities, and socio-economic status influencing compliance with water facilities and use, to effectively improve sanitation practices and enhance community health and well-being in regions with limited access to clean water like Northern Mindanao